Folate-Modified Smart Responsive Nanosystems for Enhancing Anti-Tumor Therapy Through Calcium Overload and Chemotherapy - Tang Y; Huang J; Cui C; Yang F; Li K; Gao B; Fu S; Yang X (International Journal of Nanomedicine)
Yongcheng Tang,1,2,* Jingrong Huang,3,* Cheng Cui,1,2 Fengyi Yang,1,2 Kaifu Li,1,2 Benjian Gao,1,2 Shaozhi Fu,3 Xiaoli Yang1,2 1Department of General Surgery (Hepatopancreatobiliary Surgery), The Affiliated Hospital of Southwest Medical University, Luzhou, 646000, People’s Republic of China; 2Academician (Expert) Workstation of Sichuan Province, Metabolic Hepatobiliary and Pancreatic Diseases Key Laboratory of Luzhou City, the Affiliated Hospital of Southwest Medical University, Luzhou, 646000, People’s Republic of China; 3Department of Oncology, the Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shaozhi Fu, Email shaozhifu513@163.com Xiaoli Yang, Email 344920646@qq.comObjective: The combination of DOX and 5-Fu is an important chemotherapeutic regimen but lacks targeting to solid tumor sites. Precise drug delivery via folate-modified nanomaterials is an important measure to improve efficacy and reduce toxicity.Methods: CaCO3 nanoparticles served as the carrier for loading DOX and 5-Fu, followed by encapsulation with folic acid-modified polydopamine (PDA) to form a smart dual drug-carrying nanosystem called FA-DCFP. The nanoparticles (NPs) were characterized and the release kinetics and anti-tumor effectiveness of FA-DCFP were studied in vitro and in vivo.Results: The prepared nanoparticles had an average particle size of 188.79± 0.93nm and exhibited pH-sensitive drug release. Cellular experiments demonstrated that the synergistic effect of tumor cell calcium overload and chemotherapy resulted in tumor cell death. Small animal in vivo imaging showed that FA-DCFP was well enriched in the tumour region. In vivo experiments demonstrated that FA-DCFP exhibited significant inhibition of tumour growth, attenuation of toxic side effects, and good biosafety compared to other groups.Conclusion: An intelligent-responsive nano-dual drug delivery system was developed to enhance the therapeutic effectiveness of tumors through calcium overload synergistic chemotherapy, offering a novel approach to tumor treatment.Keywords: adriamycin, calcium overload, 5-fluorouracil, drug-targeting delivery, colon cancer